THINK APP: A MOBILE APP-BASED INTERVENTION FOR ADOLESCENTS WITH FIRST-EPISODE PSYCHOSIS - Sánchez-Gutiérrez, Teresa; Barbeito, Sara; Mayoral, María; Moreno, Miguel; Rios-Aguilar, Sergio; Arango, Celso; Calvo, Ana (Schizophrenia Bulletin, 2021)
Although the use of technological advances in psychiatric treatment is relatively recent, the availability and sophistication of technologies are growing. This new therapeutic approach may provide patients with personalized, flexible, and evidence-based interventions in their communities and even in their own homes. Previous studies have shown an improvement in the access to treatment for patients with first-episode psychosis (FEP), specifically young patients, through mobile app–based interventions. The aim of this study is to develop and test the effectiveness of a mobile app–based intervention to improve community functioning in adolescents with FEP. Mobile app–based interventions could increase quality of life and disease awareness, which improve adherence to treatment and reduce the frequency of relapses and rehospitalizations in adolescents with FEP.
Keywords: JCR